2000
DOI: 10.1074/jbc.m000506200
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Composition of Inositol Trisphosphate Receptor Hetero-oligomers Expressed in COS Cells

Abstract: COS-7 cells were transiently transfected with type I and type III myo-inositol 1,4,5-trisphosphate receptor (IP 3 R) isoforms to study the processes underlying assembly and oligomerization of these tetrameric proteins. A FLAG epitope was engineered on to the N terminus of the type III IP 3 R to distinguish the transfected from the endogenous isoform. This was not necessary for the type I IP 3 R, since the endogenous levels of this isoform were extremely low. Based on sucrose gradient analysis, the transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…Briefly, to make the head subunit, IP 3 R2 cDNA in pcDNA3.1(ϩ) vector was modified so that all NcoI sites in the coding region were silently mutated (primers [15][16][17][18]. A glycine codon (GGC) was inserted after the initiation methionine to create a new NcoI site and a Kozak sequence in the context of the start codon (primer 19).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, to make the head subunit, IP 3 R2 cDNA in pcDNA3.1(ϩ) vector was modified so that all NcoI sites in the coding region were silently mutated (primers [15][16][17][18]. A glycine codon (GGC) was inserted after the initiation methionine to create a new NcoI site and a Kozak sequence in the context of the start codon (primer 19).…”
Section: Methodsmentioning
confidence: 99%
“…The InsP 3 Rs are ϳ2,700 -2,800 amino acid intracellular membrane proteins that exist as homo-or heterotetramers (209,210,212,270,311,328,363,443,536). By analogy with other cation channels and some structural information, the ion-conducting pore is believed to be created at the central axis of the tetrameric structure (Fig.…”
Section: Heteroligomerizationmentioning
confidence: 99%
“…Though heterotetramer formation between the transfected and endogenous receptor populations are possible, the vast majority of the overexpressed constructs are homotetrameric assemblies of the transfected template (17,24). Joseph et al (25) suggested that formation of the heteromeric complexes was dependent upon relative expression of the two isoforms and that there may be kinetic constraints that favor homo-oligomers over hetero-oligomers.…”
Section: Figmentioning
confidence: 99%